Percepcija duhovnosti in duhovne oskrbe v domovih starejših občanov v Ljubljani - perspektivi stanovalcev in oskrbovalcev - Gedrih, Maša (Obzornik zdravstvene nege, 2009)
Introduction: No extensive scientific research about the needs for spiritual care of patients and caregivers has yet been performed in Slovenia. The need for a broader spiritual support and a more holistic approach to treatment has already been publicly expressed, but not much action has been taken. The present legislation on the subject matter has been often times criticized for not covering the needs of the majority. Even less has been done to provide spiritual support such as regular supervision for health workers. Methods: A questionnaire was used as a data collection method. The survey was conducted among the residents and staff members of the nursing homes in Ljubljana. It focused mainly on the prevailing nature and extent of the needs for spiritual care, the type of most needed form of spiritual support, and who should provide it. Results: The results show that spiritual matters are less important for the residents than other needs. The residents perceive different forms of spirituality mainly as being in contact with nature, talking about life and praying. They prefer that spiritual care be offered by family members, friends and care givers. A person providing for their spiritual care should possess certain personal attributes or qualities, like good-heartedness, ability to listen attentively. Preferably they should also know the residents personally. Spiritual life is conceptualized in different ways - more than half of the respondents consider it as a form of religious activity, while the rest understand it in its existential sense along with thegeneral values. The staff members evaluate the actual care in nursing homesas good albeit not satisfying all the needs of the residents. For the most part they are satisfied with their jobs, but they feel that their work isnot adequately valued. They also express the need for additional support, including spiritual. (Abstract truncated at 2000 characters)
Keywords: domovi za starejše; Ljubljana; pastoralna oskrba; starejši ljudje